The Novelties of the Law of Ukraine “On Limited Liability and Additional Liability Companies” - R. S. Lukashov (Law and Safety)
One of the most common types of legal entities are companies, in particular, Limited Liability Companies, that allow to combine material and other resources of several participants and at the same time reduce the risk of entrepreneurial activity for each of them.